(untitled) (International Association of Biologicals and Computational Digest, 2022)
Plants and insects interact to each other, for food, shelter, growth and pollination. Mango leaf webber (Orthagaexvinacea) dependent on Mangifera indica L. for nourishment, classification, morphological characters and protein describe both Orthagaexvinacea and Mangifera indica L. also describe uses of mango and life cycle of Orthagaexvinacea and listed some protein of Orthagaexvinacea and Mangifera indiacaL.